1999
DOI: 10.1093/bja/82.4.531
|View full text |Cite
|
Sign up to set email alerts
|

High-dose aprotinin with gentamicin-vancomycin antibiotic prophylaxis increases blood concentrations of creatinine and cystatin C in patients undergoing coronary artery bypass grafting

Abstract: Both aprotinin and gentamicin-vancomycin antibiotic prophylaxis have been used widely in cardiac surgery to prevent bleeding and infections, respectively. As the drugs are excreted almost entirely by glomerular filtration, we investigated their action on renal function when administered either separately or together. To increase consistency, we measured serum concentrations of creatinine and cystatin C, a new marker of glomerular filtration rate, that many recent studies have shown to be more sensitive than se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Simultaneously, a decrease in arterial pressure would stimulate the renin‐angiotensin axis, causing preferential constriction of efferent arterioles, thus increasing glomerular filtration rate and urine output. Similar changes have been found in patients undergoing coronary artery bypass grafting [37].…”
Section: Discussionsupporting
confidence: 83%
“…Simultaneously, a decrease in arterial pressure would stimulate the renin‐angiotensin axis, causing preferential constriction of efferent arterioles, thus increasing glomerular filtration rate and urine output. Similar changes have been found in patients undergoing coronary artery bypass grafting [37].…”
Section: Discussionsupporting
confidence: 83%
“…Some studies investigating specifically the influence of aprotinin on renal function reported small but significant differences in renal function compared with control patients. 13 This renal impairment may be aggravated in the presence of other nephrotoxic drugs such as aminoglycosides 36 or angiotensin-converting enzyme inhibitors. 37 The influence of aprotinin on tubular function without tubular damage was confirmed by others.…”
Section: Discussionmentioning
confidence: 99%
“…First is the development of hypotension, flushing or red-man syndrome, bronchospasm, and even cardiac arrest associated with the administration of vancomycin. [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] The mechanism of action is thought to be nonimmunologic release of histamine. [50][51][52] It requires no previous exposure to vancomycin, and is classified as anaphylactoid.…”
Section: February 2007mentioning
confidence: 99%
“…In children as well as adults, cardiopulmonary bypass can modify the usual pharmacokinetics of gentamicin as a result of the greater volume of distribution secondary to priming, immature renal function, frequent use of hypothermia, ultra filtration and aprotinin, altered circulatory physiology and transient renal dysfunction. 48,[58][59][60][61][62][63] This results in the lack of a steady state and unpredictable peaks and troughs that, in turn, could have potential renal, vestibular and cochlear toxicity. [64][65][66] Additionally, there is currently no evidence to suggest a higher rate of infection with gram-negative organisms following paediatric cardiac surgery; even in those undergoing delayed sternal closure.…”
Section: Use Of Gentamicin As Antibiotic Prophylaxismentioning
confidence: 99%